PERCEPTIONS OF RELIGIOUS CULTURE AND ETHICS COURSE TEACHER CANDIDATES ON GUIDANCE - İsmail ARICI (Fırat University, 2019)
Perceptions of Guidance refers to the understanding of principles and fundamental concepts of guidance. Having a higher level of guidance knowledge would increase the accomplishments and make the goals achieved for all staffs and teachers. Therefore, it is markedly important to have this knowledge in performing guidance services for all guidance experts as well as teachers. Faculty of Theology basically instruct people for formal religious education, formal religious teaching, and informal religion services. Guidance-related courses are taught in Schools of Theology where teachers who instruct Religious Culture and Ethics Course (RCEC), elective religion courses, and Imam Hatip High School Occupational Courses graduate. Accordingly, teacher candidates are expected to have a guidance perception when they serve in the field. Consequently, their level of guidance perception is an essential issue. This study which is a quantitative research and has a causal-comparative design aims to examine the level of guidance perceptions of RCEC teacher candidates by utilizing a sample consisted of 300 senior students in Faculty of Theology at Ataturk University. We gathered the data by conducting a survey which includes Guidance Perception Inventory, socio-demographic information of the participants, and various independent variables, and used SPSS to run statistical analyses. According to the findings, teacher candidates have a high level of guidance perception. Additionally, this level differs by gender, department, and most helpful course regarding guidance perception.